Reflexiones en torno al fracaso escolar - Morales Ramírez, María Ester (2002)
This article analyzes a matter of vital importance in the current educational context: school failure. Some ideas, concepts, and experiences that are actively involved in this social problem are reviewed from different sources, and summarized, from a theoretical viewpoint. This text is divided in sections that overview the main notions on school failure magnitude of the problem in Costa Rica, associated aspects and variables derived from studies and observations among the educational and social system, and also through the family patterns and personal ways of dealing with it. This sections postulate innovative and traditional ways to visualize this problem from a holistic and multicausal perspective; proposing an interdisciplinary work to deal with an educational world full of changes and challenges.